2020
DOI: 10.1049/ipr2.12051
|View full text |Cite
|
Sign up to set email alerts
|

Dual branch convolutional neural network for copy move forgery detection

Abstract: The advent of digital era has seen a rise in the cases of illegal copying, distribution and forging of images. Even the most secure data channels sometimes suffer to validate the integrity of images. Forgery of multimedia data is devastating in various important applications like defence and satellite. Increased illegal tampering of images has paved way for research in the area of digital forensics. Copy move forgery is one of the various tampering techniques which is used for manipulating an image's content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, it is not clear whether the classifiers are biased to one class, as few papers report all four metrics: acc , P , R and F1 . For instance, in [ 29 ] the authors reported a precision of 89.0% and recall of 100%, which implies that these metrics are not balanced, and specifically, the classifier is slightly biased to the positive class.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not clear whether the classifiers are biased to one class, as few papers report all four metrics: acc , P , R and F1 . For instance, in [ 29 ] the authors reported a precision of 89.0% and recall of 100%, which implies that these metrics are not balanced, and specifically, the classifier is slightly biased to the positive class.…”
Section: Resultsmentioning
confidence: 99%
“…PRNU patterns have contributed to identify source camera [5][6][7][8][9]. Forgery localisation is achieved by abhishek et al, using semantic segmentation along with deep learning approach [10] Goel et al, used variant kernel size for dual branches to extract multiscale features that are later fused to obtain dominant features to assist classification of forged and authentic images [11]. 4 layer cnn is adopted with filter to detect splicing , copy-move [12].…”
Section: Related Workmentioning
confidence: 99%
“…Goel et al [17] also used a dual-branch CNN to capture features from tampered images. Their technique was only to detect copy-move tampering and not image splicing.…”
Section: Comparisonmentioning
confidence: 99%